Legal Protection Against Re-Uploading Videos Without Permission According to Law No.28 Of 2014: Perspective Of Content Creators' Copyright - Az Zahra Nashira Ryan; Rina Arum Prastyanti (SEAN Institute, 2025)
The development of digital technology has created a new ecosystem for content creators, especially on platforms such as YouTube, Tiktok, Instagram, Tweeter, which allows them to spread their work while earning income. This phenomenon gave rise to a trend of content commercialization known as Creatornomics, where creators not only play the role of producers of creative works, but also as actors of the digital economy(Juriadi et al., 2021). Law Number 28 of 2014 concerning Copyright provides clear legal protection for creators, including moral rights and economic rights that arise automatically after the work is realized in real form. However, behind these economic opportunities arise serious challenges in the form of rampant copyright infringement, especially the re-uploading of content by other parties without permission for commercial gain which can be subject to criminal witnesses up to 7 years in prison or fines of up to Rp.5 billion according to applicable regulations(Rinka & Irianto, 2024). The analysis of the study states that even though legal protection has been comprehensively regulated, violations still often occur due to low legal awareness in the community and the lack of optimal law enforcement on digital platforms, so efforts to improve legal education for creators, the implementation of automatic detection systems such as Content ID, and the strengthening of regulations by the government and digital platforms so that copyright protection can run optimally. Thus Creatornomics opens up new economic opportunities for content creators, but also demands increased legal literacy, supervision, and collaboration between governments, digital platforms, and society to realize a fair and sustainable creative ecosystem.